2016
DOI: 10.1186/s12872-016-0230-6
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the extent of subclinical arteriosclerosis of persons with prediabetes and diabetes mellitus among Japanese urban workers and their families: a cross-sectional study

Abstract: BackgroundDiabetes mellitus (hereafter called diabetes) is considered to accelerate arteriosclerosis leading to coronary heart disease and stroke. Thus, it is important to quantitatively estimate the extent of subclinical arteriosclerosis. A new method called cardio-ankle vascular index (CAVI) is developed to reflect arterial stiffness independently from blood pressure at the time of measurement. Then, we examined if CAVI scores could discriminate the extent of arteriosclerosis between persons with prediabetes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 12 publications
2
8
1
Order By: Relevance
“…In a study of Chinese participants free of cardiovascular disease at baseline, CAP was associated with increased CHD and stroke events during a median 10.5 year follow up [29]. Among 12 033 Japanese urban workers and their families, prediabetes mellitus were significantly associated with arterial stiffness and atherosclerosis [32]. Our study provided strong evidence that CAP significantly predicts incident CHD and stroke events in an hyperglycemia Chinese population.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…In a study of Chinese participants free of cardiovascular disease at baseline, CAP was associated with increased CHD and stroke events during a median 10.5 year follow up [29]. Among 12 033 Japanese urban workers and their families, prediabetes mellitus were significantly associated with arterial stiffness and atherosclerosis [32]. Our study provided strong evidence that CAP significantly predicts incident CHD and stroke events in an hyperglycemia Chinese population.…”
Section: Discussionmentioning
confidence: 56%
“…Prediabetes were considered to accelerate arteriosclerosis leading to coronary heart disease and stroke [30,31]. The extent of subclinical arteriosclerosis was moderately enhanced among persons with prediabetes and was further advanced among persons with diabetes [32]. Endothelial cell-specific molecule 1 (ESM-1) is a new biomarker of endothelial dysfunction, which is involved in the pathogenesis of atherosclerosis and stress induced hyperglycemia in patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetic complications involving atherosclerotic diseases have been more concerning than glucose-centric small vessel diseases 17,18 , and the advancement of arteriosclerosis among prediabetic and diabetic patients have been much faster than that in normal individuals. Another study supported that this accelerated progression of arteriosclerosis often lead to coronary heart disease and stroke 19 , reporting an increased CVD risk in IFG and DM patients with adjusted HR of 1.03 (95% CI 1.09-1.28) and 1.39 (95% CI 1.33-1.46), respectively. In line with this, our cohort study confirmed that efforts to lower blood sugar levels to normal ranges can reduce the risk of CVD.…”
Section: Discussionmentioning
confidence: 84%
“…CAVI was shown in to be high with diabetic patients in all ages ( Figure 5). Furthermore, Namekata reported that CAVI was high in prediabetic condition as well as diabetic condition [12]. Especially, CAVI showed high value in diabetic retinopathy, nephropathy and macroangiopathy.…”
Section: Cavi In Diabetic Condition and Treatmentsmentioning
confidence: 99%